Role of Pbr1, a putative oxidoreductase, in the ER quality control and folding of yeast Fks1 glucan synthase - Keisuke Obara; Hiroki Okada; Guihong Tan; Shinsuke Ohnuki; Godai Suzuki; Haruka Ohtake; Karen Kubo; Farzan Ghanegolmohammadi; Shunsuke Ishizaka; Yoko Yashiroda; Aoi Okita; Emi Mishiro-Sato; et al. (Proceedings of the National Academy of Sciences, 2026)
The biogenesis of multipass membrane proteins challenges the endoplasmic reticulum (ER) quality control, particularly when transmembrane segments contain polar or charged residues required for function. Fks1, the catalytic subunit of yeast β-(1,3)-glucan synthase, exemplifies this challenge because its large multipass transmembrane architecture must support glucan synthesis at the plasma membrane while also undergoing efficient biogenesis in the ER. Here, we investigate the cellular role of PBR1 ( YNL181W ), an essential gene whose role remains uncharacterized even though its predicted product has similarity to oxidoreductases. By integrating quantitative morphological profiling with global genetic interaction analysis, we found that PBR1 function converges on cell-wall biosynthesis and closely parallels that of FKS1 . Partial loss of Pbr1 function caused temperature-sensitive growth defects but also impaired β-(1,3)-glucan synthesis, and weakened cell-wall integrity. Under these conditions, Fks1 failed to accumulate at the cell surface and, instead, accumulated in ER-associated compartments, where it exhibited reduced stability. Biochemical analyses revealed the accumulation of immature Fks1 species, including forms defective in glycosylation, consistent with compromised ER quality control. A spontaneous missense suppressor allele of FKS1 partially restored Fks1 stability and growth, supporting a functional relationship between the two proteins. Pbr1 is a cytosol-facing ER membrane protein that physically associates with Fks1, and structural modeling suggests that it adopts a Rossmann-like fold capable of binding pyridine nucleotides despite divergence from canonical catalytic motifs. Together, these findings identify Pbr1 as an ER-associated, chaperone-like factor required for the folding and maturation of Fks1.